Pengembangan Inovatif Panel Surya Apung Pada Skala Kecil dengan Floating Berbasis Bambu Olahan di Embung Gununganyar, Kabupaten Tuban, Jawa Timur - Rasjida Amalia Bakti Lestari; Frido Ilham Prianggoro; Maya Felicia Kusnadi; Siti Kamilia Aziz (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Gununganyar Reservoir in Tuban Regency is one of the reservoirs used as a source of livelihood for the local community. However, further development and utilization of Gununganyar Reservoir have yet to be undertaken. The development of a small-scale floating Photovoltaic Solar Power Plant (floating solar panels) at Gununganyar Reservoir, aimed at providing an alternative and renewable energy source for operating raw water pumps and for supporting the Gununganyar Nature Tourism (WAG) initiative, constitutes an innovative and strategic effort to enhance energy efficiency and environmental sustainability in rural areas. This study focuses on the design and performance assessment of a floating solar panel system constructed with processed bamboo as an alternative floating material replacing HDPE, while integrating local wisdom and environmental conservation principles to minimize the reservoir’s carbon footprint. The methodology employs a simple quantitative approach combined with a literature review of relevant studies. Based on the analysis, the design of this small-scale floating solar panel system utilizes a 170 Wp off-grid solar module mounted at a tilt angle of approximately 7,1°, capable of generating a peak power output exceeding 2,962 kWp and supported by a battery capacity of 328,33 Ah. The implementation of these floating solar panels is expected to serve as a model for reservoir development by promoting energy self-sufficiency, stimulating local economic growth, and contributing to the achievement of net zero emissions by 2060.